Hierarchy of Beings and Equality of Men and Women in Catharine Trotter Cockburn's Philosophy - Calvente, Sofía Beatriz (2024)
In the early modern period the chain of being thesis was used by naturalists and philosophers to justify female subordination. My aim is to establish whether Catharine Trotter Cockburn's endorsement of this thesis entails that differences between sexes assigns differentiating places in the scale or not. I will review Locke's formulation of the ontological scale first, because Cockburn refers to his description. Locke's skepticism regarding our access to the real essence of substances hinders him from drawing unequivocal boundaries between species and even within human species. However, he states that wives must subordinate to husbands on the basis of a higher capacity and strength naturally endowed to men. Cockburn's understanding of the ontological scale rests on a realist conception where boundaries between species are clearly delimited because their nature is fixed and immutable. This insight into the ontological scale is employed to endorse natural equality between sexes, because if all members of a species share the same nature, they deserve equal treatment. Cockburn explains women subjection in terms of vicious notions and attitudes rooted in prejudice.